Pengembangan Sistem Informasi Manajemen Usaha Jasa Penggilingan Padi Gadung Dama - Thegar Septiawan Khafli; Adnan Zulkarnain (LPPM STIKI MALANG, 2022)
The high number of transactions at the Gadung Dama rice mill makes it difficult for managers to manage these transactions if done manually by telephone. This study aims to build an information system that can assist the Gadung Dama rice mill in managing the rice mill service business, namely the ordering of goods, drying registration, milling and storage of goods. The result of this research is the creation of an information system that can help manage sales of goods, make it easier for customers to find out the price of goods and stock of goods, make it easier for customers to place orders and upload proof of payment, and make it easier for customers to register for leasing services for drying, milling, and storage . In addition, this system has a queuing system to make it easier for the drying admin to manage the existing queues.